Sem fechamento, em tempo real : a produção e a recepção em blog jornalístico - Rodighero, Mateus Mecca (2015)
This study aims to discuss the relations between the new writing and reading technologies from journalistic blogs, in order to understand how readers and journalists interact in cyberspace. The study focused especially in reflecting the relations between journalism and technology, from print to digital media; understand if and how readers influence the texts of blog authors; discuss the reading statutes in digital media, specifically blogs; identify how and to what extent interaction between internet users and authors is established. To do so, a literature search was carried out, followed by field research and a case study. Literature review aimed to identify historical and conceptual elements related to the outbreak of writing, the evolution of the platforms and the reader s adaptation to the cyberspace through hypermedia. The concept was based on the texts of Lévy (1993, 1996, 1999), Santaella (2003, 2004, 2007, 2010) and Chartier (1998, 2002, 2007). It was sought to present how journalism utilized these tools and how blogs gained ground in the last decades, from Prado (2011) and Hewitt (2007). Later, in the field research, the relation existing between readers and journalists of four journalistic blogs was observed, through both systematized analysis of blogs posted to the blogosphere of an important newspaper from Porto Alegre (RS) and answers to semi-structured interviews with the authors of the columns